The impact of telemonitoring on adherence to nasal corticosteroid treatment in children with seasonal allergic rhinoconjunctivitis. Issue 10 (October 2014) - Pizzulli, A.; Perna, S.; Florack, J.; Pizzulli, A.; Giordani, P.; Tripodi, S.; Pelosi, S.; Matricardi, P. M.
Summary Background Adherence to controller therapy in allergic diseases is low. Telemonitoring has been proposed to improve adherence to treatment in chronic diseases. However, this strategy has never been tested in allergic rhinoconjunctivitis. Objective To test whether Internet‐based telemonitoring during the grass‐pollen season of children with allergic rhinoconjunctivitis may enhance adherence to treatment. Methods Children and adolescents, 5–18 years old, with moderate‐to‐severe seasonal allergic rhinoconjunctivitis to grass pollen requiring daily administration of nasal corticosteroid (NCS) (mometasone) were recruited (April 2013) in a paediatric allergy practice. Participants were randomized to Internet‐based monitoring (AllergyMonitor™, AM) or to usual care (no diary at all, controls) and followed from 13 May (T0) to 15 June 2013 (T2). An intermediate visit (T1) was performed between 31 May and 2 June. Optimal adherence to therapy was expressed as the use of at least 0.190 g/day of mometasone, corresponding to 1 puff/nostril/day, and it was measured by canister weights during (T1) and at the end (T2) of the study period. Main secondary outcomes included the reported disease severity (validated self‐questionnaire) and quality of life (AdoIRQLQ questionnaire), disease knowledge (multiple‐choice questionnaire), nasal flow and resistance at baseline and at T2. Results The use of mometasone, expressed as both optimal adherence rate (48.4% vs. 12.5%; P = 0.002) and average daily use (0.20 ± 0.12 g/day vs. 0.15 ± 0.07 g/day; P = 0.037), was higher in the AM group (n = 31) than among controls (n = 32). Disease knowledge improved among the patients using AM (83.3% vs. 68.3%; P < 0.001) but not among controls (68.2% vs. 67.7% right answers; P > 0.05). No differences were observed in the reported severity of disease, nasal flow and resistance and quality of life both at baseline and at follow‐up visits. Conclusions Internet‐based telemonitoring improves adherence to NCS treatment and disease knowledge among children and adolescents with seasonal allergic rhinoconjunctivitis.